An investigation into the curriculum ideology that foregrounds the presentation of HIV/AIDS content in selected South Africa Life Sciences textbooks - Lindelani Mnguni (SpringerOpen, 2019)
Abstract Background Research suggests that the South African school curriculum, including subjects such as Life Sciences, may be failing to address students' socio-scientific challenges such as HIV/AIDS. This could be due to the curriculum ideology that foregrounds content presented in the school subjects and related instructional designs. Given the increasing prevalence of HIV/AIDS among the youth, the present research sought to investigate the nature of HIV/AIDS presented in the curriculum together with the curriculum ideologies that foreground this knowledge. Methods A mixed-methods approach was followed in line with the realism research paradigm. Inductive document analysis was performed on five purposively selected Life Sciences textbooks to determine curriculum ideologies that foreground the presentation of HIV/AIDS knowledge. A previously validated open-ended instrument was used to generate data, which were then analyzed inductively. Results Results show that HIV/AIDS knowledge is presented in the Life Sciences textbooks as stand-alone topics and as integrated concepts in other topics. This knowledge was found to be predominantly academic. Results in this instance show that HIV/AIDS content is foregrounded by the discipline-centered ideology rather than the student and citizenship-centered ideologies, which are better suited for social justice, citizenship education, and student and social accountability. Conclusion It is concluded that the Life Sciences will probably not lead to social empowerment of student concerning HIV/AIDS.